The problem-solving method: Efficacy for learning and motivation in the field of physical education - Ezeddine, Ghaith; Souissi, Nafaa; Masmoudi, Liwa; Trabelsi, Khaled; Puce, Luca; Clark, Cain C. T.; Bragazzi, Nicola Luigi; Mrayah, Maher (Frontiers in Psychology, 2023)
Background In pursuit of quality teaching and learning, teachers seek the best method to provide their students with a positive educational atmosphere and the most appropriate learning conditions. Objectives The purpose of this study is to compare the effects of the problem-solving method vs. the traditional method on motivation and learning during physical education courses. Methods Fifty-three students (Mage 15 ± 0.1 years), in their 1st year of the Tunisian secondary education system, voluntarily participated in this study, and randomly assigned to a control or experimental group. Participants in the control group were taught using the traditional methods, whereas participants in the experimental group were taught using the problem-solving method. Both groups took part in a 10-hour experiment over 5 weeks. To measure students' situational motivation, a questionnaire was used to evaluate intrinsic motivation, identified regulation, external regulation, and amotivation during the first (T0) and the last sessions (T2). Additionally, the degree of students' learning was determined via video analyses, recorded at T0, the fifth (T1), and T2. Results Motivational dimensions, including identified regulation and intrinsic motivation, were significantly greater (all p < 0.001) in the experimental vs. the control group. The students' motor engagement in learning situations, during which the learner, despite a degree of difficulty performs the motor activity with sufficient success, increased only in the experimental group (p < 0.001). The waiting time in the experimental group decreased significantly at T1 and T2 vs. T0 (all p < 0.001), with lower values recorded in the experimental vs. the control group at the three-time points (all p < 0.001). Conclusions The problem-solving method is an efficient strategy for motor skills and performance enhancement, as well as motivation development during physical education courses.